2021
DOI: 10.1109/jphot.2021.3068529
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Tuned High-Performance III-V/Si3N4 External Cavity Laser

Abstract: Silicon nitride (Si 3 N 4) has a higher nonlinear threshold compared to silicon, which reduces the effect of two-photon absorption. However, the low thermo-optic coefficient and the reduced refractive index contrast of thin Si 3 N 4 waveguides lead to a low thermal tuning speed and low thermal efficiency. This paper demonstrates a widely tunable III-V/Si 3 N 4 hybrid-integrated external cavity laser with a relatively faster switching time. The Si 3 N 4 external feedback circuit is based on 800-nm-thick Si 3 N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Recent advances in telecom-wavelength lasing based on high-gain GaAs QDs heteroepitaxially grown on Si and SOI substrates with low thresholds and high temperature stability [282], indicate that it is a promising gain material for III-V/SiN monolithic integration and there is a strong possibility that 100 mW level heterogeneous/monolithic III-V/SiN lasers are achievable in the near future. [239,, (c) schematic layout of a heterogeneous III-V/SiN laser and its optical taper between SiN and III-V gain sections [245] and (d) development of linewidth of III-V/SiN lasers [244,246,248,249,252,254,[256][257][258][261][262][263][264]266,267,270,[272][273][274][275][276]279,280,[283][284][285].…”
Section: Iii-v/sin Integration: Towards Efficient Monolithic Lasers O...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in telecom-wavelength lasing based on high-gain GaAs QDs heteroepitaxially grown on Si and SOI substrates with low thresholds and high temperature stability [282], indicate that it is a promising gain material for III-V/SiN monolithic integration and there is a strong possibility that 100 mW level heterogeneous/monolithic III-V/SiN lasers are achievable in the near future. [239,, (c) schematic layout of a heterogeneous III-V/SiN laser and its optical taper between SiN and III-V gain sections [245] and (d) development of linewidth of III-V/SiN lasers [244,246,248,249,252,254,[256][257][258][261][262][263][264]266,267,270,[272][273][274][275][276]279,280,[283][284][285].…”
Section: Iii-v/sin Integration: Towards Efficient Monolithic Lasers O...mentioning
confidence: 99%
“…Benefiting from the fast-developing SiN devices, especially resonators with Q up to >200 M [294], a highly precise phase (factor A) and spectral (factor B) feedback [295,296] is achievable in addition to an extended cavity length (thereby reducing ∆ω 0 ), likely to generate ultranarrow linewidth. Figure 11d displays the state-of-the-art linewidth of III-V/SiN-coupled lasers in terms of integration method [244,246,248,249,252,254,[256][257][258][261][262][263][264]266,267,270,[272][273][274][275][276]279,280,[283][284][285]]. It appears that significant progress has been made with hybrid integration when compared to heterogenous/monolithic integration, though the latter started its development at a later stage.…”
Section: Iii-v/sin Integration: Towards Efficient Monolithic Lasers O...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Guo Y Y et al [35] reported a widely tunable III-V/Si 3 N 4 hybrid integrated external cavity laser. Under 500 mA injection current, the maximum output power was 34 mW.…”
Section: Silicon-based Waveguide Structure Of Nlecslsmentioning
confidence: 99%
“…It is noted that the relative frequency of the left branch is shifted towards the red side as the temperature decreases. Moreover, Since the n T of AlGaAs (2.3 × 10 −4 K −1 ) is an order of magnitude larger than those of silica and Si 3 N 4 , the on-chip thermotuning efficiency in AlGaAsOI can be much higher (∼5 GHz/ • C) than those platform , showing great efficiency for AMX operation 33 .…”
Section: Dark-pulse In An Algaasoi Microresonatormentioning
confidence: 99%